Malaysian SME's performance and the use of e-commerce: A multi-group analysis of click-and-mortar and pure-play e-retailers - Arfan Shahzad; Hon Keong Chin; Mohsin Altaf; Farooq Anwar Bajwa (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This research focuses on SMEs' adoption of e-commerce and its impact to their performance in click-and-mortar andpure-play e-retailers in Malaysia. This research framework had been developed based onResource-Based View (RBV) and Unified Theory of Acceptance & Use of Technology (UTAUT). At the same time, the combined framework contributes the new approach of studying the performance of the post adoption and factors adopting a technology. The quantitative research data were collected from 225 Malaysian SMEs operators who had adopted e-commerce. This research usescensus sampling technique to collect the data from the respondents. Then, the data were used to investigate its measurement model and structural modelvia the analysis from SPSS 20 and SmartPLS 3.0. Both categories of adoptershad the different opinion about the effort expectancy in encouraging the use of e-commerce that produces performance. Before conducting the further analysis in the group comparison via multi-group analysis (MGA), a three-step procedure, the measurement invariance of composite models (MICOM)was conducted. The result showed that among these two categories of businesses had a very different view about the effort expectancy inadopting the e-commerce. Thus, the result may provide the insight to previous researchers who had not segregated the adopters into click-and-mortarand pure-playe-commerce adopters. The research is particularly useful for practitioners by segregating thedifferent marketing strategy for the respective groups of the e-commerce adopters
Keywords: 330; Click-and-mortar; pure-play; use of e-commerce; SME performance; RBV; UTAUT; perceived risk; performance expectation; effort expectation; Malaysia